A communication-free droop control scheme for distributed linear switched reluctance wave power generation system with adaptive voltage compensation. (December 2022) - Jiang, X.S.; Hong, Yue; Chen, Kaiwen; Cheung, Norbert; Wai Eric Cheng, Ka; Pan, J.F.
Highlights: The droop control strategy has been studied for distributed energy storage and generation system based on three energy storage units. The innovative droop algorithm is proposed to regulate compensation factor of bus voltage through real time adaptive voltage compensation. The effectiveness of the proposed controller is verified through experiments considering the external disturbances. Abstract: In wave energy generation systems, scaled and improved energy extraction can be realized by utilizing distributed linear switch reluctant generators (LSRGs). However, this type of power generation system often employs supercapacitors (SCs) as the energy storage media, and the system often suffers from output voltage variation and current fluctuation from the LSRGs. Meanwhile, the fixed droop factor also causes bus voltage deviation and aggravates energy imbalance of the energy storage system. In this paper, a communication-free droop control scheme with adaptive voltage compensation is proposed for the distributed linear switched reluctance wave power generation system. First, system stability is improved by applying a high droop factor. When the bus voltage fluctuation exceeeds the compensator threshold, this voltage information of the energy storage unit is introduced into the control loop. In addition, an adaptive voltage compensation algorithm is proposed for the system, and the control algorithm is able to reduce the bus voltage deviation and the energy imbalance of the storage unit, caused by the droop factor. The proposed control strategy can further improve the response and reliability of the energy storage units, and the bus voltage fluctuation can be regulated within ±3%.